Murtad dalam Perspektif Fikih, Teologi, dan Hak Asasi Manusia - Rahmah, Miftahur; Zainuddin, Zainuddin (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
This study examines apostasy from the perspective of jurisprudence, theology and human rights. Freedom in choosing beliefs is the right of all humans. Even in Human Rights (HAM) it has been mentioned about basic human rights in detail, one of which is freedom of interest and religion. Not only in human rights, the law in Indonesia is the same. In Islam also regulates freedom of religion. But what is happening today is the issue of apostasy, which is an important issue in Islam. This study often occurs among Muslims and is a very sensitive issue because someone who leaves Islam or is called an apostate will disturb the feelings and harmony of many parties as well as the harmony of the community. This study aims to determine how apostasy is in the perspective of fiqh, theology and human rights. This type of research is library research. Data were collected through books and journal articles related to research. The results of this study indicate that there is no compulsion in adhering to religious beliefs. A person has the freedom to choose Islam or anything else. However, if someone has made his choice to Islam, then there is no freedom to choose anymore, that person must obey and obey the teachings of Islam in a kaffah (comprehensive) manner. There are penalties and sanctions for those who violate.